Evaluating the Effectiveness of Gamification on Students’ Performance in a Cybersecurity Course (Journal of The Colloquium for Information Systems Security Education, 2020)
The motivation of students to actively engage in course activities has significant impact on the outcome of academic courses. Prior studies have shown that innovative instructional interventions and course delivery methods have a vital role in boosting the motivation of students. Gamification tools aid course delivery by utilizing well established game design principles to enhance skill development, routine practice and self-testing. In this article, we present a study on how the use of a course gamification platform dubbed OneUp impacts the motivation of students in an online cyber security course. The study shows that more than 90% of the respondents agreed that OneUp has improved the effectiveness of the course delivery. In addition, 75% of the respondents want to use OneUp in their future courses. Furthermore, our analysis shows that OneUp has improved the median grade of students from B+ to A- compared to the same course delivered the previous year without using OneUp.
Keywords: cybersecurity education; gamification; self-learning; oneup